Correction to: Combining health insurance funds in a fragmented context: what kind of challenges should be considered? - Mohammad Bazyar; Arash Rashidian; Minoo Alipouri Sakha; Mohammad Reza Vaez Mahdavi; Leila Doshmangir (BMC, 2020)
In the original publication of this article [1], there are two corrections: